Pengelolaan Media Pembelajaran di Sekolah Dasar Negeri 62/III Mukai Mudik - Ayuni Shakila; Febi Tria (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
The purpose of this study was to describe the planning, utilization, and maintenance of instructional media in SDN 62/III Mukai Mudik. The research is a qualitative research design with phenomenology. Sources in the research is the principal and teachers at SDN 62/III Mukai Mudik. Data collection technique were interview, observation and documentation. Analysis of data using an interactive model. This study has three outcomes: (1) Planning the learning media is an inventory of types of instructional media, relevancing teaching media to teaching materials, confirming media with other teachers or friends of the group, preparing a book support package from the government, and pour the planned use of the media in the learning device; (2) The use of instructional media is able to show a medium of learning makes the students more easily understand the teaching materials, instructional media were able to show increasing curiosity about the new sciences, capable of showing the learning media help teachers explain the learning material, and be able to demonstrate learning media reduces verbal learning theory; (3) Maintenance of instructional media is keeping the medium of learning material or objects in special cabinets, learning media in the form of a file stored on the computer, non-academic learning media such as marching band and tambourine are stored in a special room, and the media is damaged beyond repair maintenance direct teachers or experts.